2013
DOI: 10.1016/j.msec.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, mechanical property and corrosion behaviors of interpenetrating C/Mg-Zn-Mn composite fabricated by suction casting

Abstract: A novel interpenetrating C/Mg-Zn-Mn composite was fabricated by infiltrating Mg-Zn-Mn alloy into porous carbon using suction casting technique. The microstructure, mechanical properties and corrosion behaviors of the composite have been evaluated by means of SEM, XRD, mechanical testing and immersion test. It was shown that the composite had a compact structure and the interfacial bonding between Mg-Zn-Mn alloy and carbon scaffold was very well. The composite had an ultimate compressive strength of (195 ± 15) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The particle size, morphology, surface area, crystalline framework, and composition are responsible of the optoelectronic properties of ZnO [18][19][20][21][27][28][29][30][31] including the photocatalytic activity. Properties of ZnO-based materials are highly dependent of the synthesis method [18][19][20][21][27][28][29][30][31][36][37][38][39][40][41][42] including viscosity of slurry suspensions [18,20,27], Pechini synthesis [28,42], polymeric precursor degradation [29], sol-gel following annealing [19], microwave-assisted solvothermal synthesis [31], high-energy ball-milling [36], spray pyrolysis [37], suction casting [39], and hydrothermal synthesis [21,38,40,41], among others. These set of works have shown that ZnO is a versatile ceramic material, which can be used in several applications such as solar cells [31], varistors [36], luminescent materials [37], and photocatalysts [18]…”
Section: Introductionmentioning
confidence: 99%
“…The particle size, morphology, surface area, crystalline framework, and composition are responsible of the optoelectronic properties of ZnO [18][19][20][21][27][28][29][30][31] including the photocatalytic activity. Properties of ZnO-based materials are highly dependent of the synthesis method [18][19][20][21][27][28][29][30][31][36][37][38][39][40][41][42] including viscosity of slurry suspensions [18,20,27], Pechini synthesis [28,42], polymeric precursor degradation [29], sol-gel following annealing [19], microwave-assisted solvothermal synthesis [31], high-energy ball-milling [36], spray pyrolysis [37], suction casting [39], and hydrothermal synthesis [21,38,40,41], among others. These set of works have shown that ZnO is a versatile ceramic material, which can be used in several applications such as solar cells [31], varistors [36], luminescent materials [37], and photocatalysts [18]…”
Section: Introductionmentioning
confidence: 99%
“…304 Several interesting studies have been performed to prepare Mg matrix composites using this technique. [305][306][307][308][309] Ma et al have applied this technique to prepare a biodegradable b-TCP/Mg-Ca composite. 306 In this study, they initially created the interconnected porous b-TCP scaffolds by coating PU foams with b-TCP via slurry coating and sintering at 1100°C to burn out PU foam.…”
Section: Infiltrationmentioning
confidence: 99%
“…The (HA + β-TCP)/Mg-5Sn interpenetrating composite was prepared by infiltrating the molten Mg-5Sn alloy into the porous HA + β-TCP scaffold using a self-made vacuum suction casting equipment described elsewhere [21]. Firstly, the porous HA + β-TCP scaffold was positioned in the vacuum suction casting equipment, which was pre-pumped to −0.07-−0.05 MPa.…”
Section: Materials Preparationmentioning
confidence: 99%